PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN NAGAN RAYA - Zarman, Nasri; Karollah, Banta; Rusnawati, Rusnawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2024)
The purpose of this research was to determine the effect of work environment and workload on the work productivity of employees of the Population and Civil Registration Service of Nagan Raya Regency, both partially and simultaneously. The number of samples in this study was 54 employees. This research method is a quantitative method. Research data were collected through questionnaires. Research data were analyzed using multiple linear regression models and processed using the SPSS (Statistical Product and Service Solutions) assistance program. Hypothesis testing used the t test and F test. The results of this study partially showed that the work environment partially had a positive and significant effect with a tcount value (5.222) greater than ttable (2.008) with a significance of 0.020 and workload had a partial positive and significant effect where the tcount value (5.003) was greater than the ttable value (2.008) with a significance of 0.001. Based on the F test, the results show that the work environment and workload simultaneously have a positive and significant effect on the work productivity of employees of the Population and Civil Registration Service of Nagan Raya Regency with Fcount (5.963) greater than Ftable (3.179) with a significance of 0.001. It can be concluded that both partially and simultaneously the work environment and workload have a positive and significant effect on work productivity. It is expected that the Population and Civil Registration Service of Nagan Raya Regency, pays attention to the work environment and workload to increase employee work productivity.